Mitochondrial neurogastrointestinal encephalomyopathy: Case report - Yaşar ÇOLAK; İlyas TUNCER and Erkan Çağlar and Dilek BARUTÇU and Celal ULAŞOĞLU and Şafak KIZILTAŞ (Turkish Journal of Gastroenterology, 2019)
-